PENGARUH LATIHAN MENDORONG BOLA BASKET KE ATAS TERHADAP PENINGKATAN PASING ATAS PADA OLAHRAGA EKSTRA KURIKULER BOLA VOLI SMA N 1 BANGOREJO TAHUN PELAJARAN 2018/2019 - Achmad Zayul Mustain; Agus Mursidi (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2019)
The aims of this  study is to examine the passive ability of volleyball extra-curricular students at Bangorejo High School 1 N to find out the Pasing ability of volleyball and try to improve the ability of the upper pas, in this case the researcher will study using the theory of overload that is given training giving to students must be heavier than the previous exercise, in this case the researcher uses the basketball method, why is that because the weight of the basketball is much heavier than the volleyball. The number of respondents was 30 students who followed the volleyball extracurricular extracurricular activity at Bangorejo Public High School in Banyuwangi District by using quantitative methods through an approach using t test analysis techniques and obtained results. 1 BANGOREJO Academic Year 2018/2019. From the pretest data the mean 24.4 at the time of the posttest average reached 28.8. The magnitude of the change in the above passing ability can be seen from the difference in the average value that is equal to 4.1.